BASLAWÍSH KLASS OQÍWSHÍLARÍNDA FIZIKALÍQ SAPALARDÍ RAWAJLANDÍRÍWDA MILLIY OYÍNLARDÍŃ ROLI - Allayarov, M.J.; Joldasbaev, P.M. (ILIM hám JÁMIYET, 2017)
The article deals with the issues of development of physical qualities of pupils in using national games in primary classes and what national games may be included in the educational process. The author of the article presents some moving games corresponding to pupils’physical gualities.